Neuropsychological study of anxiety-depression, personality profile and quality of life in patients with vertebral and peripheral nerve pathology - Llaja Rojas, Victoria (2016)
The objective of the present investigation was to describe and analyze the disorders of the personal psychic activity of patients with vertebral pathology and peripheral nerves; and explain the commitment of their functional activity through the sociobiological theoretical model of personality (MOS). The sample consisted of all the patients diagnosed by the specialist physician, who presented a recurrent episode of intense pain at the cervical, lumbar o discal level in Dxs. Which does not return with common analgesics or Physical Therapy Rehabilitation and are treated in the service of vertebral column and peripheral nerves. The sampling was intentional nonprobabilistic, and data were collected during the period June 2015 to January 2016. The design was descriptive, observational, crosssectional, and retrospective, clinical trial type. The revised POC -2005 Neuropsychological Battery was administered (Sarria, Llaja y García, 2008), as well as specialized Personality Profile (SNP) and Quality of Life Questionnaire from Bahia 2008) and the findings were interpreted using the SOP Model. The results indicate that there is a positive correlation between depression and anxiety in surgically operated patients of the spine. It was also observed that the predominant personality profile is that of anxiety presenting the highest level with 25.5 %, followed by the type of immature personality with 22.2 %.